Simultaneous Determination of Plant Growth Regulators in Fruits Using a Modified QuEChERS Procedure and UPLC–MS/MS - Zhen Yan; Jiyun Nie; Guofeng Xu; Haifei Li; Jing Li; Zhixia Li; Yonglong Wu; Lixue Kuang (Horticultural Plant Journal, 2016)
Six plant growth regulators frequently used in fruit were detected using UPLC–MS/MS including chlormequat chloride, GA3, forchlorfenuron, paclobutrazol, thidiazuron and 2,4-D. A modified QuEChERS method was used in pretreatment: each compound was extracted with acetonitrile containing 1% acetic acid and cleaned with a mixture of ostade-cylsilane (ODS) and MgSO4. The detection was performed using electrospray ionization (ESI) and multiple reaction monitoring mode (MRM) and quantified using the external standard method. Results indicated that the calibration curves of six plant growth regulators were linear within the range of 1–100 µg⋅kg-1 with correlation coefficients over 0.999. The recovery at four spiked concentrations, 1, 20, 50, and 100 µg⋅kg-1, ranged from 60.77% to 119.43% and relative standard deviation (RSD) were between 0.18% and 32.94%. The limits of detection (LOD) and limits of quantitation (LOQ) were 0.01–0.14 µg⋅kg-1 and 0.02–0.46 µg⋅kg-1, respectively, for apples, 0.01–0.18 µg⋅kg-1 and 0.03–0.59 µg⋅kg-1 for grapes, 0.01–0.08 µg⋅kg-1 and 0.04–0.28 µg⋅kg-1 for kiwis, 0.003–0.110 µg⋅kg-1 and 0.01–0.38 µg⋅kg-1 for peaches, and 0.01–0.08 µg⋅kg-1 and 0.03–0.25 µg⋅kg-1 for oranges.